DETERMINATION OF NCD64, MHLA-DR, AND SI IN FULL-TERM NEWBORNS WITH SEPSIS AT VIETNAM NATIONAL CHILDREN’S HOSPITAL (2019 - 2021) - Tran Tat Thang; Hoang Dinh Canh (JOURNAL OF CONTROL VACCINES AND BIOLOGICALS, 2023)
The study was conducted to determine the role of nCD64, mHLA-DR and SI in the diagnosis of neonatal sepsis. The study was designed using experimental descriptive research method at the laboratory. Mean values of nCD64, mHLA-DR and SI in full-term newborns with sepsis were 10167.1 ± 6136.9 molecules/cell, 9898.4 ± 14173,9 molecules/ cell, and 274.6 ± 287.5 respectively. SI and nCD64 had high values in the diagnosis of sepsis in full-term newborns (AUC = 0.8, p < 0.01), higher than that of CRP, platelets and white blood cells. The sensitivity and specificity of SI at the SI cut-off point > 29.1 were 95.1% and 41.2%, respectively. The sensitivity and specificity of nCD64 at the nCD64 cut-off point 5004 were 88.2% and 44.5%, respectively. SI and nCD64 are highly valuable in the diagnosis of sepsis in full-term newborns (AUC = 8, p < 0.01).